PENTINGNYA ADMINISTRASI GUNA MENINGKATAKAN MUTU - Nurhadi, M.HI (LIPI, 2014)
School administration is all the effort to serve, help and meet together to leverage resources, both personal and material, effectively and efficiently in order to support the achievement of optimal schooling. The importance because it serves as the School Administration: planning, organizing, coordinating, communication, supervision, staffing, financing and assessment aimed at improving the quality of education or learning in school. Development of school administration planning format.